Isolation of Triterpenoids Onion Sabrang (Eleutherine bulbosa) and Antibacterial Activity Tests of Escherichia Coli - Rahmawati, Nadya Fitri; Sakinah, Sakinah; Hasbi, Hasbi (International Journal of Multidisciplinary Research of Higher Education, 2018)
Research on the isolation and antibacterial activity test of the Sabrang Onion (Eleutherine bulbosa) bulb has been carried out. This study aims to obtain triterpenoid compounds from Sabrang onion bulb and find out its activity as an antibacterial against Escherichia coli bacteria causing Urinary Tract Infection (UTI). UTI is a disease with a fairly high prevalence of 80% caused by E. coli bacteria, with the highest number of patient are woman. The stages of this research include extraction by maceration method using n-hexane solvent. The concentrated n-hexane extract was then analyzed with thin layer chromatography. Positive identification of triterpenoids was carried out using Liebermann-Burchard reagents with n-hexane: ethyl acetate (9: 1) eluent. The obtained isolates were also analyzed using UV-Vis spectrophotometry. The results of the analysis showed that the isolate had an absorbance value of 0.205 A at a wavelength of 443 nm and 0.430 A at a wavelength of 788 nm. The isolates were tested for antibacterial activity against E. coli bacteria by agar diffusion method. The results showed that the inhibition zone diameter at a concentration of 0.5% w / v was 20.19 mm, at a concentration of 1% w / v the inhibitory zone was 21.83 mm. In the positive control used standard tetracycline, the diameter of the inhibition zone was 40.67mm. Inhibition zone diameter at a concentration of 0.5% w / v was 20.19 mm, at a concentration of 1% w / v the resulting inhibition zone was 21.83 mm. An increase in the response of inhibition against E. coli bacteria with a concentration of 1% w/ v of 1.64 mm. In the positive control, the diameter of inhibition zone is 40.67 mm. Thus, triterpenoid isolates from Sabrang Onion are effective as antibacterial, in the strong category with inhibition zone diameters > 20 mm.